2021
DOI: 10.22209/ic.v62n4a09
|View full text |Cite
|
Sign up to set email alerts
|

Cáncer y Microbiota

Abstract: El cuerpo humano está expuesto continuamente a microorganismos tanto fijos como transitorios, así como sus metabolitos tóxicos, lo cual puede conducir a la aparición y progresión del cáncer en sitios distantes al hábitat particular de cada microbio. Diversos estudios científicos han hecho posible entender la relación estrecha que existe entre microbioma y cáncer, ya que los componentes del primero, al tener la capacidad de migrar a diferentes zonas del cuerpo, pueden contribuir al desarrollo de diversas enferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 166 publications
0
7
0
4
Order By: Relevance
“…Dysbiosis of the microbiome is closely associated with OSCC [ 38 ]. Previous studies confirmed alterations in the oral microbiome of OSCC, but the results were controversial [ 16 ]. Quantitatively analysing the compositional alterations in the oral microbiome of OSCC using a meta-analysis have not been performed yet to resolve the issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysbiosis of the microbiome is closely associated with OSCC [ 38 ]. Previous studies confirmed alterations in the oral microbiome of OSCC, but the results were controversial [ 16 ]. Quantitatively analysing the compositional alterations in the oral microbiome of OSCC using a meta-analysis have not been performed yet to resolve the issue.…”
Section: Discussionmentioning
confidence: 99%
“…This sequencing provides a more comprehensive and accurate method to describe the microbiome during health and disease. To date, studies have found that a number of bacteria in the oral microbiome are associated with OSCC [ 16 ]. However, the results of these studies fluctuate owing to differences in design, sample size, and sites.…”
Section: Introductionmentioning
confidence: 99%
“…Solid tumors often exhibit low oxygen levels or hypoxia, a prevalent characteristic that can substantially impact cellular metabolism. [52][53][54] Under hypoxic conditions, cells rely on anaerobic glycolysis to produce energy, leading to an accumulation of lactate and reduced oxidative phosphorylation. [52][53][54] This transition in metabolism can exert an influence over NAD(P)H levels within live cells.…”
Section: Nad(p) Detection In Live Cellsmentioning
confidence: 99%
“…[52][53][54] Under hypoxic conditions, cells rely on anaerobic glycolysis to produce energy, leading to an accumulation of lactate and reduced oxidative phosphorylation. [52][53][54] This transition in metabolism can exert an influence over NAD(P)H levels within live cells. NADH generation transpires during glycolysis, whereas NAD(P)H assumes a pivotal role in upholding redox equilibrium and biosynthesis pathways.…”
Section: Nad(p) Detection In Live Cellsmentioning
confidence: 99%
See 1 more Smart Citation